Rate of infection following revision anterior cruciate ligament reconstruction and associated patient‐ and surgeon‐dependent risk factors: Retrospective results from MOON and MARS data collected from 2002 to 2011. Issue 2 (19th October 2020) - ; Brophy, Robert H.; Wright, Rick W.; Huston, Laura J.; Haas, Amanda K.; Allen, Christina R.; Anderson, Allen F.; Cooper, Daniel E.; DeBerardino, Thomas M.; Dunn, Warren R.; Lantz, Brett (Brick) A.; Mann, Barton; et al.
Abstract: Infection is a rare occurrence after revision anterior cruciate ligament reconstruction (rACLR). Because of the low rates of infection, it has been difficult to identify risk factors for infection in this patient population. The purpose of this study was to report the rate of infection following rACLR and assess whether infection is associated with patient‐ and surgeon‐dependent risk factors. We reviewed two large prospective cohorts to identify patients with postoperative infections following rACLR. Age, sex, body mass index (BMI), smoking status, history of diabetes, and graft choice were recorded for each patient. The association of these factors with postoperative infection following rACLR was assessed. There were 1423 rACLR cases in the combined cohort, with 9 (0.6%) reporting postoperative infections. Allografts had a higher risk of infection than autografts (odds ratio, 6.8; 95% CI, 0.9–54.5; p = .045). Diabetes (odds ratio, 28.6; 95% CI, 5.5–149.9; p = .004) was a risk factor for infection. Patient age, sex, BMI, and smoking status were not associated with risk of infection after rACLR.